Comparison of Early Versus Delayed Oral β Blockers in Acute Coronary Syndromes and Effect on Outcomes - Bugiardini, Raffaele; Cenko, Edina; Ricci, Beatrice; Vasiljevic, Zorana; Dorobantu, Maria; Sasko Kedev; Marija Vavlukis; Oliver Kalpak; Puddu, Paolo Emilio; Gustiene, Olivija; Trninic, Dijana; Knežević, Božidarka; et al. (Elsevier BV, 2016)
The aim of this study was to determine if earlier administration of oral β ​blocker therapy in patients with acute coronary syndromes (ACSs) is associated with an increased short-term survival rate and improved left ventricular (LV) function. We studied 11,581 patients enrolled in the International Survey of Acute Coronary Syndromes in Transitional Countries registry from January 2010 to June 2014. Of these patients, 6,117 were excluded as they received intravenous β blockers or remained free of any β ​blocker treatment during hospital stay, 23 as timing of oral β ​blocker administration was unknown, and 182 patients because they died before oral β blockers could be given. The final study population comprised 5,259 patients. The primary outcome was the incidence of in-hospital mortality. The secondary outcome was the incidence of severe LV dysfunction defined as an ejection fraction <40% at hospital discharge. Oral β blockers were administered soon (≤24 hours) after hospital admission in 1,377 patients and later (>24 hours) during hospital stay in the remaining 3,882 patients. Early β ​blocker therapy was significantly associated with reduced in-hospital mortality (odds ratio 0.41, 95% CI 0.21 to 0.80) and reduced incidence of severe LV dysfunction (odds ratio 0.57, 95% CI 0.42 to 0.78). Significant mortality benefits with early β ​blocker therapy disappeared when patients with Killip class III/IV were included as dummy variables. The results were confirmed by propensity score-matched analyses. In conclusion, in patients with ACSs, earlier administration of oral β ​blocker therapy should be a priority with a greater probability of improving LV function and in-hospital survival rate. Patients presenting with acute pulmonary edema or cardiogenic shock should be excluded from this early treatment regimen.
Keywords: Acute Coronary Syndrome; Beta-Blockers; Timing; In-hospital mortality